The 2014 Scottish Referendum in the Chinese imagination. Issue 2 (May 2019) - Hua, Minchao
Abstract : This paper lays out the perceptions of three different regions to describe Chinese perspectives on the 2014 Scottish Independence Referendum. Mainstream newspapers, cyber-opinions, and scholarly writings are three vectors to assess Mainland Chinese perception. Considering the limited number of academic reports about the referendum in Taiwan and Hong Kong, compared to that on the mainland, our conclusion about their perceptions is primarily based on mainstream newspapers. The article identifies two ideologically opposed perspectives. On the one hand, the dominant view in Mainland China (and in mainstream newspapers in Hong Kong and Taiwan) framed the referendum in negative terms, presenting it as a 'threat' and a 'problem'. On the other hand, the dominant view in Hong Kong and Taiwan praised the Scottish referendum as a model of participatory democracy. These contrasting perspectives are deeply rooted in distinctive ideologies and historical experiences.